Does market inclusion empower women? Evidence from Bangladesh - Raghunathan, Kalyani; Ramani, Gayathri V.; Rubin, Deborah; Pereira, Audrey; Ahmed, Akhter; Malapit, Hazel J.; Quisumbing, Agnes R. (International Food Policy Research Institute, 2021)
Increased market inclusion through participation in agricultural value chains may increase employment and household incomes, but evidence on its empowerment impacts is mixed. In societies with restrictive social norms, greater market inclusion can enhance existing income and empowerment inequalities by relegating marginalized groups, including women, to low value chains or lower value nodes within those chains. We use primary data from rural Bangladesh to investigate the associations between households’ primary economic activity – agricultural wage-earning, production, or entrepreneurship – and absolute and relative levels of men’s and women’s empowerment. Women in producer households, on average, fare better on empowerment outcomes than women in wage-earner or entrepreneur households; the opposite is true for men. The gap between men’s and women’s empowerment scores is also lowest in producer households. A decomposition of these results into composite indicators yields insights into potential trade-offs, while accompanying qualitative work highlights the importance of social and cultural norms in shaping the economic roles women can adopt. With a push towards diversification of agriculture into higher value market-oriented crops, more careful programming is needed to ensure that market inclusion translates into an increase in women’s empowerment.